Conceptual Space of Image in the Psychological Literature - Bilyk, T. M. (Psychological Prospects Journal, 2011)
The results of theoretical analysis of concept image are highlighted in the article. Theoretical conclusion of main conceptual lines of image definition and structure is proposed.